Admission Management System of Bestlink College of the Philippines for Senior High School: Vol.3, No.1D (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The admission management system in BCP enables students to enroll on their subjects before the commencement of their semesters. This Admission Management system allows international students to enroll online without travelling to the campus and incorporates the business rules. These business rules cover a wide range of regulations and policies such as subject pre-requisite, student's payment status, course coordinator's decision and the correspondence of students' seniority to the intended enrolling subjects. Besides business rules, the system incorporates notifications like Short Messaging Service (SMS) and Email. XML is used to store the business rules and thus allow the portability of the system interface to a wider range of devices, such as Personal Device Assistant (PDA). (Patrick H. H., 2006) The interface auto-detects the user's device, either a PC/laptop or a smaller screen device such as a PDA. In short, the Admission Management system's backend engine runs based on business rules, and the front-end engine runs to provide a high-satisfaction user experience. With the business and user interface, the system can run the workflow of student Admissions from the online Admission form to the approval workflow cycle running parallel with the notification capability. Categories and Subject Descriptors H.4 [Information Systems Applications]: Miscellaneous General Terms Management, Human Factors, Standardization. Keywords Enrollment, SMS, Email, Web Application System. The online registration system, on the one hand, sounds simple as a straightforward procedure; on the other hand, it is a complicated workflow that is based on strict university enrollment rules. These enrollment rules are a subset of the university’s business rules. These rules cover subject prerequisites, the student’s payment status, the course coordinator’s decision and the student’s seniority. These business rules are used by the online student Admission Management system. The data collection instruments were interviews to solicit information from students, faculty officers and staff of the programming unit of MUCG, and some of the university’s registration records were examined. DFD, Use Case Diagrams and Sequence diagrams were used to model the existing and proposed system. PHP and MySQL were the tools used to develop the system. In the current system, a student having to register must first come to the school to go through the processes. Students are expected to deposit cheques or bank drafts at the cash office before a slip is printed out to take to the Faculty Officer. At the bank, students' queue for long hours and at the registration centers (faculties). During the registration, each student is asked to provide basic personal information, such as their index number, to begin the registration process. The student’s personal information obtained is fed into the registration system. The faculty/Registration Officer then checks to see if the details given by the student are correct. Then there is a selection of courses. The student is then handed the registration printout and made to append his signature to a book to confirm his registration. The printout shows the date and time of registration, the courses registered, and the number of credit hours allocated for each course. The student must check the courses registered to be sure those are the ones he has to offer for the semester.